Ketahanan Beberapa Galur Harapan Kacang Hijau Asal Kepulauan Tanimbar Terhadap Penyakit Busuk Akar Basah (Rhizoctonia Solani Kuhn) - Laritmas, Irma S; Leiwakabessy, Christoffol; Raharjo, Simon H.T (Universitas Pattimura, 2024)
Mung bean is a supplemental and alternative food source whose disease attacks often hamper cultivation. One of the main diseases that attacks mung beans is wet root rot caused by R. solani, which has a negative effect on growth and causes a decrease in crop yield. This research aimed to determine mung bean lines resistant to wet root rot disease and the level of resistance of the lines from the Tanimbar Islands to wet root rot disease. This research was carried out at the Disease Diagnosis Laboratory, Pattimura University, and took place from July to September 2023. It used descriptive analysis involving eight treatments in the form of 8 local mung bean genotypes from the Tanimbar Islands. The R. solani isolate used to test the resistance of mung bean genotypes was taken from samples of diseased plants (mustard), isolated on PDA media, and grown for seven days. The genotypes that were tested by inoculation at the seedling stage consisted of KC_3-8, KC_6-1, KC_8-2, KC_9-10, KC_23-6, KC_23-8, KC_23-9, and KC_26-4. In addition to the growth of young seedlings after inoculation, the parameters as indicators of mung bean resistance were the incubation period and disease severity in each genotype. Analyses of the incubation period, severity of wet root rot disease, and vegetative plant growth data consisting of sprout height, number of leaves, root length, and fresh and dry weight, were carried out descriptively. The results of this study indicate that three genotypes were moderately susceptible to R. solani, namely KC_6-1, KC_3-8, and KC_9-10; whereas the genotypes KC_26-4, KC_23-6, KC_25-8, KC_25-8, KC_28-9 were included in the susceptible category. The lowest root rot disease severity was found in genotypes KC_6-1, KC_3-8, and KC_9-10, while the other five genotypes were in the high category.